Pressure Buildup Monitoring of the Krafla Geothermal Field, Iceland - Sigurdsson, Omar; Steingrimsson, Benedikt S.; Stefansson, Valgardur (Orkustofnun, Grensasvegur 9, 108 Reykjavik, Iceland, 1985)
A break in electrical power generation from the Krafla geothermal plant was planned from beginning of May to early September 1984. Early in June most of the production wells were shutin and their pressure recovery monitored. A regular monitoring of the pressure buildup was carried out on a well to well basis until mid-August, when the wells were put back into production except for wells 12 and 16. They were used to monitor the pressure drawdown due to the start of production. This was abruptly brought to an end by a nearby volcanic eruption in early September. The pressure buildup in the two-phase geothermal reservoir at Krafla is described and the first results presented. The results are compared with parameters determined on the completion of the wells and with predictions from numerical simulations of the reservoir. Finally the status of the Krafla geothermal system is discussed with regard to the comparison.